Active Involvement In Organizations, Hobbies, And Self-Discipline: Determining Factors Of Students' Academic Success - Gusta, Wienda; Mukhaiyar, Mukhaiyar; Gistituati, Nurhizrah; Zakirman, Zakirman (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
ABSTRACTThe research aims to explore the relationship between involvement in organizations, hobbies, self-discipline, and academic success of students at the Faculty of Computer Science (FILKOM) Universitas Putra Indonesia (YPTK) Padang, especially students who are in the Sixth Semester. It applies a correlational quantitative approach with a cross-sectional design to identify the relationship between these variables. The research sample consisted of 150–200 students selected randomly using simple random sampling techniques. Data was collected through an online questionnaire, which included questions regarding organizational involvement, hobbies, self-discipline, and academic achievement. The research results show that involvement in organizations, hobbies, and self-discipline have a significant relationship with students' academic success. The results of multiple linear regression analysis show that these three factors together can explain 46% of the variation in student academic success. Involvement in organizations contributes to improving social and managerial skills, hobbies play a role in maintaining psychological well-being and managing stress, and self-discipline helps students to stay focused and avoid procrastination. This research provides important insight that to achieve academic success, students need to develop involvement in organizations, positive hobbies, and self-discipline in a balanced way. Suggestions are given for educational institutions to provide facilities and programs that holistically support this third factor's development.